3521 Distinct single cell gene expression in peripheral blood monocytes correlates with treatment response groups to TNF-alpha inhibition in rheumatoid arthritis. (27th March 2019) - Muskardin, Theresa Wampler; Jin, Zhongbo; Dorschner, Jessica M.; Ghodke-Puranik, Yogita; Niewold, Timothy
Abstract : OBJECTIVES/SPECIFIC AIMS: The cellular mechanisms that underlie the IFNβ/α ratio that predicts response are not known. Effects of IFN on single immune cells may be masked in whole blood or mixed cell populations. By studying the effect of IFNβ/α activity ratio on individual monocytes, we can determine the functional impact of the IFN ratio and suggest the cellular mechanisms that underlie response/non-response to TNFi therapy in RA. METHODS/STUDY POPULATION: We used single cell analysis to investigate whether monocyte gene expression differs significantly between RA patients according to their pre-TNFi serum IFN-β/α ratio. Single classical (CL) and non-classical (NC) blood-derived monocytes were isolated from 15 seropositive RA subjects prior to biologic therapy. Subjects were grouped by pre-TNFi serum IFN-β/α ratio into two groups, those with a high IFN-β/α ratio (≥1.3, n = 6) and those with a low IFN-β/α ratio (<1.3, n = 9). 87 target genes were analyzed. Genes that varied significantly between the groups by categorical analyses were tested in multivariate logistic regression models. RESULTS/ANTICIPATED RESULTS: Every participant was seropositive for rheumatoid factor and antibodies to cyclic citrullinated peptide. Among the participants in the groups, there were no significant differences in age or DAS scores (P>0.05). The treatments were comparable and none were being treated with biologic therapy. There were striking differences in monocyte gene expression between patients with pre-treatment blood IFNβ/α activity <1.3 and ≥1.3. Expression of (1) key type I IFN pathway genes (JAK1, STAT2, IFIT2, IFIH1, PRDM1); (2) IL12; (3) CD36; and (4) CTLA4 were the strongest differentiators between groups (p<0.0001 for each, corrected for multiple comparisons). DISCUSSION/SIGNIFICANCE OF IMPACT: In this study we were able to measure gene expression in single monocytes from seropositive RA patients prior to biologic treatment. Within-cell co-expression patterns demonstrate biological differences in monocytes of RA patients with an IFNβ/α ≥1.3, the ratio of type I IFNs which predicts non-response to TNFi. The data suggest that there may be differential IFN production and pathway activation in patients who do not respond to TNFi. The increased expression of CD36 in monocytes from RA patients with high IFN β/α activity may be a reflection of increased "foam cells" in the inflamed tissue of patients who do not respond to TNFi. Enrichment of CTLA4 in those with high serum IFNβ/α suggests that CTLA4-Ig may be less likely to be an effective alternative for someone who is not likely to respond to TNFi. Current work includes determining whether the peripheral blood findings reflect altered cellular composition, type I IFN production and signaling in the synovium. Significance: This work will help to develop a more individualized approach to therapy in RA and determine an immunological basis of response/non-response to TNFi.